2014
DOI: 10.1155/2014/508583
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Peak Pressure Index Parameters for People with Spinal Cord Injury Using Wheelchair Tilt-in-Space and Recline: Methodology and Preliminary Report

Abstract: The purpose of this study was to determine the effect of the sensel window's location and size when calculating the peak pressure index (PPI) of pressure mapping with varying degrees of wheelchair tilt-in-space (tilt) and recline in people with spinal cord injury (SCI). Thirteen power wheelchair users were recruited into this study. Six combinations of wheelchair tilt (15°, 25°, and 35°) and recline (10° and 30°) were used by the participants in random order. Displacements of peak pressure and center of pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…In addition, Kwon and colleagues compared the average pressure change according to the reclining wheelchair angle in 20 healthy 20-year-old men from a neutral posture of 90°. There were no differences at 100° and 110°, but a large difference was observed at 120° [4,19]. Previous studies have demonstrated that pressure can be reduced by maintaining an angle of 120° or more, but this study confirmed a significant pressurereducing effect even at 110°.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, Kwon and colleagues compared the average pressure change according to the reclining wheelchair angle in 20 healthy 20-year-old men from a neutral posture of 90°. There were no differences at 100° and 110°, but a large difference was observed at 120° [4,19]. Previous studies have demonstrated that pressure can be reduced by maintaining an angle of 120° or more, but this study confirmed a significant pressurereducing effect even at 110°.…”
Section: Discussioncontrasting
confidence: 51%
“…While maximal tilt and recline angles of other studies were limited to 35°T and 30°R [ 17 , 22 ], Aissaoui et al . [ 21 ] remains the only investigation other than the current in which mean sitting pressure was analysed up to 45°T and 30°R.…”
Section: Discussionmentioning
confidence: 99%
“…This grid size was chosen due to its geometric inclusion of heel contact area without significant effects of adjacent, zero-force sensel frames. The 3 × 4 grid creates a 19.35 cm 2 sensel window, meeting the recommended 9 -10 cm 2 minimal measurement area for contact force determination on skin [21] [22]. The masking frame was used to only select data corresponding to heel to be exported from the MeasureX software.…”
Section: Methodsmentioning
confidence: 99%